Fostering Lifelong Learning: Interplay of Self-Concept and Self-Regulation among Adolescents: Membangun Pembelajaran Seumur Hidup: Interaksi Antara Konsep Diri dan Regulasi Diri pada Remaja - Kurniawan, Adhitya; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2023)
This correlational quantitative study investigates the relationship between self-concept and self-regulation in learning among middle school students. With a sample of 270 respondents from SMPN 2 Taman Sidoarjo, employing proportional stratified random sampling, the research utilizes the Pearson correlation test for analysis. The study reveals a positive association between students' self-concept and self-regulation in learning (r = 0.357; p > 0.05). The independent variable contributes 12.7% to the dependent variable, implying that 87.3% of variance is attributed to other factors. These findings emphasize the significance of nurturing a positive self-concept alongside promoting self-regulation strategies to enhance students' cognitive development and long-term learning success. Highlights: Positive Self-Concept and Learning Success: This study explores the positive relationship between self-concept and self-regulation in learning among adolescents, highlighting the impact of a positive self-concept on students' overall learning outcomes. Quantitative Correlation Analysis: Utilizing a correlational quantitative approach, the research investigates the interplay between self-concept and self-regulation, offering insights into the strength of their association within the context of student learning. Promoting Lifelong Learning Skills: The findings underscore the need to foster a positive self-concept and provide effective self-regulation strategies to adolescents, as these factors contribute significantly to cognitive development and long-term learning success. Keywords: Self-concept, Self-regulation, Learning outcomes, Adolescents, Correlational research.